Analisis Kandungan Zat Pengawet Boraks Pada Sampel Jajanan Bakso di Desa Jatipurno Kabupaten Wonogiri - Winny Swastike; Shanti Emawati; Ayu Intan Sari (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2015)
Wonogiri an area that is well known as an area where people are dominated by traders meatballs. Type meatballs offered vary from meatballs served with noodles in the form of soup or meatballs are sold singly or known as grilled meatballs. Things are very concerned about is the use of borax in meatballs often functioned as chewing of food. Borax poisoning can occur through food, one of which is meatballs as one type of food that is very familiar. This study aimed to analyze the content of borax in food, especially meatballs in Jatipurno village, Wonogiri. This type of research is descriptive laboratory with laboratory tests are qualitative and quantitative methods of flame with acid-base titration method. The population is all hawker meatballs in Jatipurno village, Wonogiri. Sample was taken by purposive sampling of each meatball sellers. The experimental results on samples compound identification borax meatballs with flame method, note that of the 50 samples tested meatballs did not produce a green flame which means not detected borax content in the samples. The final conclusion is that the meatballs were analyzed by flame proving that the sample was circulated in Jatipurno village, Wonogiri is not identified free of borax and borax content. Not to do quantitative research to determine levels of borax meatballs snacks for the qualitative research produces a negative value (does not contain borax). Keywords: Food Additives, meatball snacks, borax